2023
DOI: 10.1002/pbc.30321
|View full text |Cite
|
Sign up to set email alerts
|

Revaccination of children with acute lymphoblastic leukemia following completion of chemotherapy

Abstract: Background: Intensive chemotherapy for acute lymphoblastic leukemia (ALL) may affect the immune system and potentially the immune memory causing antibodies provided by vaccination to disappear. There are disagreements regarding the guidelines for posttreatment immunization strategy.Methods: Ninety-six children (aged 1-18 years at diagnosis) who completed chemotherapy for ALL were recruited. Antibody levels in the patient's serum against measles, varicella, polio, pertussis, hepatitis A, and hepatitis B were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A recent study in children who completed chemotherapy for hematolymphoid malignancies showed loss of vaccine-acquired immunity, with >57% of children showing seronegativity for measles. 37 Therefore, irrespective of previous vaccine status, children with hematolymphoid malignancies are susceptible to measles because of their immunosuppressed state. Protection by offering herd immunity is the best way to prevent measles in children receiving immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in children who completed chemotherapy for hematolymphoid malignancies showed loss of vaccine-acquired immunity, with >57% of children showing seronegativity for measles. 37 Therefore, irrespective of previous vaccine status, children with hematolymphoid malignancies are susceptible to measles because of their immunosuppressed state. Protection by offering herd immunity is the best way to prevent measles in children receiving immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%